Acute kidney injury following autoimmune hemolytic anemia due to simultaneous use of ciprofloxacin and hydrochlorothiazide: A case report and review of the literature. Issue 1 (27th February 2023) - Yaghoubi, Fatemeh; Tavakoli, Farnaz; Dalil, Davood; Jamaloo, Hoda
Abstract: Introduction: Rare cases of autoimmune hemolytic anemia (AHA) associated with using ciprofloxacin or hydrochlorothiazide (HCTZ) alone have been reported before. However, simultaneous use of both drugs could lead to a severe clinical condition. This study presents the combination of acute kidney injury (AKI) and AHA following the simultaneous use of ciprofloxacin and HCTZ for three days. Case Description: A 42‐year‐old Iranian woman presented to the emergency department with symptoms of fatigue, lethargy, nausea and vomiting, ataxia, oliguria, dark urine, and jaundice. The patient reported using HCTZ due to high blood pressure and ciprofloxacin for a urinary tract infection three days before presentation. Early laboratory findings revealed hemolytic anemia with a hemoglobin of 7 g/dl, the strongly positive direct and indirect Coombs test, high level of lactate dehydrogenase (820 IU/L), and hyperbilirubinemia (total: 3 mg/dL and direct: 1.2 mg/dL). Furthermore, hyperkalemia (5.2 mEq/L), hyperphosphatemia (6.2 mg/dL), high levels of BUN (100 mg/dL), and creatinine rise (6.8 mg/dL) were found. Urine analysis showed 2+ blood, 4‐6 red blood cells, and cola‐colored urine. Based on the findings, drug‐induced AHA, followed by AKI, was diagnosed. Following, the drugs were stopped and steroid therapy was initiated. The patient underwent four sessions of hemodialysis to improve the AKI. Conclusion: Healthcare providers should be aware of the life‐threatening adverse effects of commonly used drugs such as ciprofloxacin or HCTZ. The timely diagnosis of the offending drugs leads to avoiding the persistence of the risk factor and the deterioration of the patient's clinical condition. Abstract : The mechanisms by which drugs induce immune hemolytic anemia are classified into drug‐dependent and drug‐independent categories. Highlights: The combination of hemolytic anemia and acute kidney injury following the concomitant use of ciprofloxacin and hydrochlorothiazide is a rare and severe complication presented in this study. Healthcare providers should be aware of the life‐threatening drug‐induced autoimmune hemolytic anemia that may occur with commonly used drugs. The treatment mainly includes cessation of the offending drug, steroid therapy, blood transfusion if needed, and supportive care.